Pengaruh Keterampilan Manajerial Kepala Madrasah, Kompensasi Guru dan Kompetensi Profesional Guru terhadap Kinerja Guru MTs - Mahram Mahram; Muhammad Muhammad; Ribahan Ribahan (PALAPA, 2023)
The quality of education that has not been maximized, especially in East Lombok Regency, is influenced by many things, including teacher performance. Teacher performance is influenced by internal factors (competence, motivation, morale, discipline) and external (physical environment, leadership of the madrasa principal, managerial implementation of the madrasa principal, compensation, work culture). This study aims to examine the influence of the managerial skills of madrasa heads, compensation and professional competence of teachers on teacher performance. This study uses a quantitative approach to the type of comparative causal research or expost pacto. The sample of this study was 176 teachers from private Madrasah Tsanawiyah in Aikmel District, East Lombok Regency. The research instrument was a questionnaire which was given to the respondents directly after testing the validity and reliability. Data analysis techniques used simple regression tests and multiple regression tests followed by correlation tests (with the help of the SPSS version 22.0 application). The results of data analysis based on the value of the correlation coefficient and determination for each research variable on teacher performance obtained the determination coefficient of madrasa principal managerial skills of 0.324 and 10.5%, teacher compensation of 0.298 and 8.9%, and teacher professional competency variable of 0.711 and 50.5%. While the results of the coefficient of determination together obtained by 52.3%. Thus, it can be stated that: 1) The managerial skills of madrasa principals affect teacher performance; 2) teacher compensation affects teacher performance; 3) teacher professional competence influences teacher performance; and 4) the managerial skills of madrasa heads, teacher compensation and teacher professional competence jointly affect teacher performance.